2019
DOI: 10.1093/conphys/coz040
|View full text |Cite
|
Sign up to set email alerts
|

Reference intervals for blood-based biochemical analytes of southern Beaufort Sea polar bears

Abstract: Accurate reference intervals (RIs) for commonly measured blood-based analytes are essential for health monitoring programmes. Baseline values for a panel of analytes can be used to monitor physiologic and pathophysiologic processes such as organ function, electrolyte balance and protein catabolism. Our reference population includes 651 serum samples from polar bears (Ursus maritimus) from the southern Beaufort Sea (SB) subpopulation sampled in Alaska, USA, between 1983 and 2016. To establish RI for 13 biochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…We also observed annual changes in biomarkers linked to liver function. In clinical veterinary medicine, small increases in liver enzyme activity are often masked by wide reference intervals (Fry et al, 2019) with pathologic concerns indicated by at least a twofold or greater change in enzyme activity. Although we did not see multifold increases in ALT, it significantly increased with capture year in both male and female bears (Appendix S2, Figure 6).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We also observed annual changes in biomarkers linked to liver function. In clinical veterinary medicine, small increases in liver enzyme activity are often masked by wide reference intervals (Fry et al, 2019) with pathologic concerns indicated by at least a twofold or greater change in enzyme activity. Although we did not see multifold increases in ALT, it significantly increased with capture year in both male and female bears (Appendix S2, Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…We further explored the extent to which differences in summer habitat selection (i.e., use of land versus sea ice), breeding status of females, and short-term fasting status influenced physiologic biomarkers. Because demographic characteristics of polar bears and season affect physiology (Atwood, Peacock, et al, 2016;Derocher et al, 1990;Fry et al, 2019; Kirk et al, 2010a;Rode et al, 2017;Rode, Regehr, et al, 2021;Whiteman et al, 2015Whiteman et al, , 2018, we included sex, age, and denning status, as well as season of capture and year as co-variates in our analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We suggest it is unlikely there is evidence of age-driven variation in Malay civet renal performance, as urea levels did not vary with animal age, as would be clinically expected from renal complications. Similar patterns were documented in Iberian lynx ( Beltrán et al, 1991 ; García et al ., 2010 ), Amur leopard ( Bodgener and Lewis, 2017 ), polar bear ( Ursus maritimus, Fry et al, 2019 ) and Chinese pangolin ( Manis pentadactyla, Khatri-Chhetri et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%